2005
DOI: 10.1079/ecp200438
|View full text |Cite
|
Sign up to set email alerts
|

The effect of herbal supplementation on the severity of exercise-induced pulmonary haemorrhage

Abstract: Exercise-induced pulmonary haemorrhage (EIPH) is a serious condition that affects the health and possibly the performance of all racehorses. However, only two treatments, furosemide and the Flair™ equine nasal strip, both of which reduce capillary transmural pressure, have been successful in reducing EIPH. Alternatively, transient impairment of platelet function and coagulation during exercise has been considered an additional contributor to EIPH. Consequently, herbal formulations designed to enhance platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Bronchoalveolar lavage (BAL) has been utilized for a little over a decade in horses to evaluate the concentration of RBC present in the BAL fluid post-exercise 51 , and is frequently referred to in the equine 2,3,[17][18][19]22,[45][46][47][48][49] and human literature 7,89 to quantify the degree or severity of EIPH. An advantage of BAL is that there is not a precise window of time within which BAL has to be performed, as is the case with endoscopy 2,90 .…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bronchoalveolar lavage (BAL) has been utilized for a little over a decade in horses to evaluate the concentration of RBC present in the BAL fluid post-exercise 51 , and is frequently referred to in the equine 2,3,[17][18][19]22,[45][46][47][48][49] and human literature 7,89 to quantify the degree or severity of EIPH. An advantage of BAL is that there is not a precise window of time within which BAL has to be performed, as is the case with endoscopy 2,90 .…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Even though King et al 8,9 did visualize small amounts of bleeding in two dogs with endoscopy, the relatively low [RBC] in BAL observed post-race in the current study would not likely have been observed with endoscopy 1,2,51,92 . The 2 h post-race lavage was chosen versus 30 min post-race as is conventional in the equine literature 2,3,[17][18][19]22,[45][46][47][48] and similar to the King studies 8,9 due to the increased safety of transporting the dogs back to the veterinary teaching hospital for the procedure instead of anaesthetizing the dogs at the track. The 2 h post-race lavage was chosen versus 30 min post-race as is conventional in the equine literature 2,3,[17][18][19]22,[45][46][47][48] and similar to the King studies 8,9 due to the increased safety of transporting the dogs back to the veterinary teaching hospital for the procedure instead of anaesthetizing the dogs at the track.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is emerging evidence that haemostatic agents, such as aminocaproic acid and conjugated oestrogens may, via their antifibrinolytic effects (Heidmann et al 2005), also decrease the severity of EIPH (H. H. Erickson and T. S. Epp, unpublished data). In contrast to the above, neither inhaled nitric oxide (irrespective of lowering pulmonary artery pressure, Kindig et al 2001b) nor herbal formulations designed to remedy putative coagulation defects (Epp et al 2005)…”
mentioning
confidence: 97%